The effect of weight reduction rate on body composition, thyroid hormones and basal metabolic rate in elite athletes - Koivisto, A.; Garthe, I.; Sundgot-Borgen, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Optimal body composition and body weight (BW) are important performance factors in sports that emphasize aesthetics and high power to weight ratio. Weight reduction guidelines for athletes today suggest a weekly weight loss of 0.5-1.0kg which corresponds to 0.7% and 1.4% of BW in a 70-kg athlete (1). Weight reduction may lead to loss of lean body mass (LBM) and changed thyroid hormone profile and thereby reduced basal metabolic rate (BMR). Combining resistance training with energy restriction may reduce loss of LBM in overweight subjects (2). Purpose: To compare changes in body composition, thyroid hormones and BMR in two different weight-loss interventions promoting loss of 0.7% versus 1.4% of BW per week in elite athletes. Methods: 30 male and female elite athletes were randomized in to slow weight reduction ["SLOW", n=14, 23.5± 3.3y, 72.1± 12.2kg] and fast weight reduction ["FAST", n=16, 22.3± 4.7y, 72.2±11.3kg]. Both interventions included energy restricted diets and resistance training regimen for 6-12 weeks. The duration was dependent on the desired weight loss and the random allocation to one of the interventions. Diets were recorded by a 4-day weighed food records which were used to design individual meal plans promoting weekly BW loss of 0.7% or 1.4%. Four weekly resistance training sessions were added to the usual training regimen to stimulate muscle hypertrophy. The following measurements were taken at the baseline and post intervention: BW, LBM, FM with dual energy x-ray absorptiometry (DEXA), s-THS and s-free T4 and BMR with indirect calorimeter. Results: There were no significant differences between the groups in any variables at the baseline. BW was reduced by (5.6± 3.0%, p<0.001) and (5.4± 2.3%, p<0.001) for SLOW- and FAST-group, respectively. The changes were not significantly different between the groups (p=0.8). LBM was significantly increased for SLOW (2.0± 1.3%, p<0.001) but not for FAST (1.1± 3.0%, p=0.3). There was a significant difference in change of FM between the groups SLOW (-31± 2.9%, p<0.001) and FAST (-23.4± 13.8%, p<0.001)(p=0.04). Free T4 reduction was significant in FAST (-11.2± 7.6% , p=0.001) but not in SLOW. These changes were significantly different between the groups (p<0.001). BMR reduced significantly for both SLOW (-12.3± 11.4%, p=0.036) and FAST (-9.8± 6.5%, p=0.018), but did not differ between the groups (p=0.9). Conclusion: For optimal body composition changes in athletes a moderate energy restriction combined with resistance training leading to a weekly weight loss of 0.7% seems preferable. Despite maintained or increased LBM, athletes experienced reductions in BMR.